Inverse problems in engineering mechanics International Symposium on Inverse Problems in Engineering Mechanics 1998 (ISIP '98), Nagano, Japan - Tanaka, M. (Masataka), 1943-; Dulikravich, George S.
Inverse problems can be found in many topics of engineering mechanics. There are many successful applications in the fields of inverse problems (non-destructive testing and characterization of material properties by ultrasonic or X-ray techniques, thermography, etc.). Generally speaking, the inverse problems are concerned with the determination of the input and the characteristics of a mechanical system from some of the output from the system. Mathematically, such problems are ill-posed and have to be overcome through development of new computational schemes, regularization techniques, objective functionals, and experimental procedures. Seventy-two papers were presented at the International Symposium on Inverse Problems in Mechanics (ISIP '98) held in March of 1998 in Nagano, where recent developments in the inverse problems in engineering mechanics and related topics were discussed. The main themes were: mathematical and computational aspects of the inverse problems, parameter or system identification, shape determination, sensitivity analysis, optimization, material property characterization, ultrasonic non-destructive testing, elastodynamic inverse problems, thermal inverse problems, and other engineering applications.